Local Site Effects and Incremental Damage of Buildings During the 2016 Central Italy Earthquake Sequence. Issue 4 (November 2018) - Sextos, Anastasios; De Risi, Raffaele; Pagliaroli, Alessandro; Foti, Sebastiano; Passeri, Federico; Ausilio, Ernesto; Cairo, Roberto; Capatti, Maria Chiara; Chiabrando, Filiberto; Chiaradonna, Anna; Dashti, Shideh; De Silva, Filomena; et al.
The Central Italy earthquake sequence initiated on 24 August 2016 with a moment magnitudeM 6.1 event, followed by two earthquakes (M 5.9 andM 6.5) on 26 and 30 October, caused significant damage and loss of life in the town of Amatrice and other nearby villages and hamlets. The significance of this sequence led to a major international reconnaissance effort to thoroughly examine the effects of this disaster. Specifically, this paper presents evidences of strong local site effects (i.e., amplification of seismic waves because of stratigraphic and topographic effects that leads to damage concentration in certain areas). It also examines the damage patterns observed along the entire sequence of events in association with the spatial distribution of ground motion intensity with emphasis on the clearly distinct performance of reinforced concrete and masonry structures under multiple excitations. The paper concludes with a critical assessment of past retrofit measures efficiency and a series of lessons learned as per the behavior of structures to a sequence of strong earthquake events.